Sistem Rekomendasi Investasi Dengan Metode Berbasis Pembobotan Linear Simple Additive Weighting dan Rank Order Centroid Model - Savitri, Savitri; Waluyo, Iwan Giri; Rosyani, Perani (Journal Global Technology Computer, 2025)
Investment is a strategic activity for managing and growing wealth, whether for short-term or long-term purposes. However, selecting the appropriate investment instrument is not straightforward, as each asset has unique characteristics, including risk level, liquidity, and maintenance costs. This study aims to develop an investment recommendation system using a Multi-Criteria Decision Making (MCDM) approach, specifically by combining the Simple Additive Weighting (SAW) method and the Rank Order Centroid (ROC) technique. The five investment alternatives evaluated in this research are gold bullion, property, luxury jewelry, artwork, and classic cars, assessed against six main criteria: return on investment (ROI), liquidity, risk, maintenance cost, popularity & demand, and availability (scarcity). The ROC method is applied to determine objective weights based on expert-ranked preferences, followed by normalization and scoring of each alternative using the SAW method. The results indicate that gold bullion achieves the highest score (0.882) and is the most recommended investment. This model successfully provides transparent and systematic recommendations and can be further enhanced with dynamic market data and a broader range of investment alternatives.